FMR1 premutation frequency in a large, ethnically diverse population referred for carrier testing. Issue 6 (31st March 2018) - Owens, Kailey M.; Dohany, Lindsay; Holland, Carol; DaRe, Jeana; Mann, Tobias; Settler, Christina; Longman, Ryan E.
Abstract : Fragile X syndrome (FXS) is the most common inherited cause of intellectual disability and is caused by an expansion of cytosine‐guanine‐guanine (CGG) repeats in the FMR1 gene. Female premutation allele carriers (55–200 CGG repeats) are at risk to have an affected child. Currently, specific population‐based carrier screening for FXS is not recommended. Previous studies exploring female premutation carrier frequency have been limited by size or ethnicity. This retrospective study provides a pan‐ethnic estimate of the Fragile X premutation carrier frequency in a large, ethnically diverse population of women referred for routine carrier screening during a specified time period at Progenity, Inc. Patient ethnicity was self‐reported and categorized as: African American, Ashkenazi Jewish, Asian, Caucasian, Hispanic, Native American, Other/Mixed/Unknown, or Sephardic Jewish. FXS test results were stratified by ethnicity and repeat allele category. Total premutation carrier frequency was calculated and compared against each ethnic group. A total of 134, 933 samples were included. The pan‐ethnic premutation carrier frequency was 1 in 201. Only the Asian group differed significantly from this frequency. Using the carrier frequency of 1 in 201, a conservative pan‐ethnic risk estimate for a male fetus to have FXS can be calculated as 1 in 2, 412. This risk is similar to the highest ethnic‐based fetal risks for cystic fibrosis and spinal muscular atrophy, for which population‐wide screening is currently recommended. This study adds to the literature and supports further evaluation into specific population‐wide screening recommendations for FXS.